Bimetallic sulfide particles incorporated in Fe/Co-based metal–organic framework ultrathin nanosheets toward boosted electrocatalysis of the oxygen evolution reaction. Issue 13 (18th May 2022) - Yu, Rui; Wang, Cheng; Liu, Dongmei; Wu, Zhengying; Li, Jie; Du, Yukou
Abstract : CoFe-MS/MOF nanocatalysts consisting of interconnected MOF ultrathin nanosheets doped with metal sulfide particles are prepared via a facile one-step solvothermal method as efficient electrocatalysts for the OER. Abstract : The development of inexpensive, high-performance, and long-lasting electrocatalysts toward the oxygen evolution reaction (OER) has been proved to be crucial to enhance the efficiency of water splitting to obtain clean and sustainable energy. Herein, Fe/Co-based metal–organic framework (MOF) ultrathin nanosheets doped with (Fe)-Co3 S4 metal sulfide (MS) particles (CoFe-MS/MOF) are reported as superior electrocatalysts for the OER. CoFe-MS/MOFs exhibit an outstanding OER performance with a small overpotential of 261 mV and a low Tafel slope of 60.3 mV dec −1 at a current density of 10 mA cm −2 while showing high durability in an alkaline medium. The existence of metal sulfide particles plays a pivotal part in promoting the charge transfer capacity as well as the formation of ultrathin MOF nanosheets. More significantly, they can also modulate the adsorption energy of oxygenated intermediates, thereby significantly enhancing the inherent electrocatalytic activity. This work provides guidance for rationally designing and synthesizing inexpensive and highly active bimetallic sulfide doped MOF electrocatalysts in the electrochemical energy field.